Comparison of Energy Efficiencies for Advanced Anaerobic Digestion, Incineration, and Gasification Processes in Municipal Sludge Management - Gorgec, A. Gezer; Insel, G.; Yagci, N.; Dogru, M.; Erdincler, A.; Sanin, D.; Filibeli, A.; Keskinler, B.; Cokgor, E. U. (DEStech Publications, 2016)
Municipal sludge has energy content in the range of (9,000–23,000 kJ/kg)depending upon the organic content. This entrapped energy can be transformed intoheat and electrical energies by different technologies combining biological and thermalprocesses. Recently, the combination of advanced digestion and incineration or gasificationwas found to be advantageous for energy recovery. The energy balance was basedupon a full-scale wastewater treatment plant (WWTP) using conventional and advancedtreatment configurations. In this respect, the unit electricity production from sludge wascalculated to be in the range of 675–1,240 kWhE per tones of dry solids.